2022
DOI: 10.3390/biomimetics7040143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diclofenac and Simvastatin on Bone Defect Healing—An In Vivo Animal Study

Abstract: Non-steroidal, anti-inflammatory drugs and statins are two widely prescribed drug classes that affect bone formation. The aim of this study was to elucidate the effect of diclofenac and simvastatin in artificial bone defect healing. One hundred and forty-four male Wistar rats were used, and the specimens were divided into groups, with respect to the route of drug administration and the type of defect healing (with or without collagen membrane), and subgroups, with respect to the study duration (2, 4 or 8 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
6
1
Order By: Relevance
“…Regarding the Sim group, at week 2, the results showed better effects for bone formation compared to the Co group, which agrees with the results of Zhao et al [ 55 ]. However, after 4 weeks, the results of the study showed that there was no effect of Sim when compared to the Co group, disagreeing with the results of Karanikola et al [ 56 ]. The variance in the results is mostly attributed to the difference in the study model and experimental site.…”
Section: Discussioncontrasting
confidence: 83%
“…Regarding the Sim group, at week 2, the results showed better effects for bone formation compared to the Co group, which agrees with the results of Zhao et al [ 55 ]. However, after 4 weeks, the results of the study showed that there was no effect of Sim when compared to the Co group, disagreeing with the results of Karanikola et al [ 56 ]. The variance in the results is mostly attributed to the difference in the study model and experimental site.…”
Section: Discussioncontrasting
confidence: 83%
“…Its known that the systemic administration of DCS has a negative effect on bone healing in animals [ 39 ]. As local medication, however, 5% IBP and 5% DCS associated with Ca(OH) 2 pastes have shown low cytotoxicity in a mouse pre-osteoblast cell line [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A median sagittal incision was made along the top of the skull, parietal bones were exposed, and two circular calvarial bone defects, 1‒2 mm in thickness, were created on both sides of the sagittal suture, with a 6-mm-diameter trephine drill at 1500 rpm under saline irrigation to prevent excessive heating ( Figure 1 ). 40 According to the study of Porto et al 41 in 2012, this size of the defects is critical for the 15-day evaluation period. Then, the periosteum and skin were carefully sutured with 4-0 silk (skin) and 4-0 vicryl (periosteum).…”
Section: Methodsmentioning
confidence: 99%
“…Based on our pilot study, 40 we considered that the primary outcome (defect regeneration percentage) in the control group would be approximately 20 ± 10%. Based on this, to detect a difference of ± 15% between the groups, at least seven animals would be needed in each group to reach a power (1-β) of 0.80, with α = 0.05.…”
Section: Methodsmentioning
confidence: 99%